Aquiles e Ájax: a 'poesis' da alteridade na ânfora de Exéquias - Figueira, Ana (2017)
This research offers a rereading of Exekias' vase showing Achilles and Ájax. We argue that this theme alludes to alterity and time and we show how some literary concepts are key to this rereading.